Telomere length, telomere‐related genes, and breast cancer risk: The breast cancer health disparities study. Issue 7 (30th April 2013) - Pellatt, Andrew J.; Wolff, Roger K.; Torres‐Mejia, Gabriela; John, Esther M.; Herrick, Jennifer S.; Lundgreen, Abbie; Baumgartner, Kathy B.; Giuliano, Anna R.; Hines, Lisa M.; Fejerman, Laura; Cawthon, Richard; Slattery, Martha L.
<x xml:space="preserve">Abstract</x> Telomeres are involved in maintaining genomic stability. Previous studies have linked both telomere length (TL) and telomere‐related genes with cancer. We evaluated associations between telomere‐related genes, TL, and breast cancer risk in an admixed population of US non‐Hispanic white (1, 481 cases, 1, 586 controls) and U.S. Hispanic and Mexican women (2, 111 cases, 2, 597 controls) from the Breast Cancer Health Disparities Study. TL was assessed in 1, 500 women based on their genetic ancestry. TL‐related genes assessed were MEN1, MRE11A, RECQL5, TEP1, TERC, TERF2, TERT, TNKS, and TNKS2. Longer TL was associated with increased breast cancer risk [odds ratio (OR) 1.87, 95% confidence interval (CI) 1.38, 2.55], with the highest risk (OR 3.11, 95% CI 1.74, 5.67 p interaction 0.02) among women with high Indigenous American ancestry. Several TL‐related single nucleotide polymorphisms had modest association with breast cancer risk overall, including TEP1 rs93886 (OR 0.82, 95% CI 0.70, 0.95); TERF2 rs3785074 (OR 1.13, 95% CI 1.03, 1.24); TERT rs4246742 (OR 0.85, 95% CI 0.77, 0.93); TERT rs10069690 (OR 1.13, 95% CI 1.03, 1.24); TERT rs2242652 (OR 1.51, 95% CI 1.11, 2.04); and TNKS rs6990300 (OR 0.89, 95% CI 0.81, 0.97). Several differences in association were detected by hormone receptor status of tumors. Most notable were associations with TERT rs2736118 (ORadj 6.18, 95% CI 2.90, 13.19) with estrogen receptor negative/progesterone receptor positive (ER−/PR+) tumors and TERT rs2735940 (ORadj 0.73, 95% CI 0.59, 0.91) with ER−/PR− tumors. These data provide support for an association between TL and TL‐related genes and risk of breast cancer. The association may be modified by hormone receptor status and genetic ancestry. © 2013 Wiley Periodicals, Inc.